Design and performance analysis of a simplified hybrid modulation method for dual active bridge powering inverters - Mohamad Fathi Mohamad Elias; Intan Mastura Saadon; Norridah Amin (PLoS ONE, 2026)
This paper presents a simplified hybrid modulation method for operating dual-active-bridge (DAB) converters that power inverters by integrating single-phase shift (SPS) and triple-phase shift (TPS) modulation schemes. It covers the design and control algorithm development, performance analysis, as well as highlights its benefits and limitations. While full TPS implementation is highly complex, this work selects a specific TPS operating mode to enhance DAB converter efficiency in low-power conditions with minimal control effort. In the proposed method, a hysteresis controller is employed to regulate the DAB modulation at a defined power threshold. This poses a significant challenge, especially when a single proportional-integral (PI) controller is employed to regulate output power with a minimal set of control parameters applicable to both modulation schemes. Moreover, in addressing these challenges, a trade-off between high efficiency and fast dynamic response is also considered, with greater emphasis placed on efficiency when developing the controllers. Meanwhile, the inverter output voltage is independently controlled regardless of the DAB operation to further simplify the overall process. Small signal modeling and closed-loop control of DAB-based inverter with the proposed hybrid modulation are also presented. Its functionality and performance have been verified through simulation and a developed small-scale DAB-based inverter prototype.